PENGARUH KETIDAKAMANAN KERJA DAN KUALITAS KEHIDUPAN KERJA TERHADAP KEINGINAN BERHENTI KERJA MELALUI STRES KERJA PADA KARYAWAN PT. CHEVRON PACIFIC INDONESIA DI PETAPAHAN PROVINSI RIAU - Rudiyanto Rudiyanto (Jurnal Ekonomi, 2018)
The study conducted in PT. Chevron Pacific Indonesia site office Petapahan and aimed to know the influence of job insecurity and quality work of life towards intention to quit, as well as the mediating effect of job-related stress. Population are PT. Chevron Pacific Indonesia site office Petapahan permanent staff consist of 105 employees. Samples taken by census that consists of 105 employees. Variables used are job insecurity and quality work of life as independents, intention to quit as dependent, while job-related stress used as intervening variabel. Data analyzed by using descriptive and SEM-PLS that assisted by Warp-PLS 5.0. The study reveals that job insecurity significantly influences quality work of life, but not significant towards intention to quit. Quality work of life has significant influence towards intention to quit. Job-related stress mediates the impact of  job insecurity and quality work of life towards intention to quit. Reducing the insecurity along with enhancing the quality work of life may potentially decreased the job-related stress and intention to quit among employees.